Patient-reported outcomes and final overall survival results from the randomized phase 3 PENELOPE trial evaluating pertuzumab in low tumor human epidermal growth factor receptor 3 (HER3) mRNA-expressing platinum-resistant ovarian cancer. Issue 7 (15th August 2019) - Lorusso, Domenica; Hilpert, Felix; González Martin, Antonio; Rau, Joern; Ottevanger, Petronella; Greimel, Elfriede; Lück, Hans-Joachim; Selle, Frédéric; Colombo, Nicoletta; Kroep, Judith R; Mirza, Mansoor R; Berger, Regina; et al.
Abstract : Introduction: The PENELOPE trial evaluated pertuzumab added to chemotherapy for biomarker-selected platinum-resistant ovarian cancer. As previously reported, pertuzumab did not statistically significantly improve progression-free survival (primary end point: HR 0.74, 95% CI 0.50 to 1.11), although results in the paclitaxel and gemcitabine cohorts suggested activity. Here, we report final overall survival and patient-reported outcomes. Patients and methods: Eligible patients had ovarian carcinoma that progressed during/within 6 months of completing ≥4 platinum cycles, low tumor human epidermal growth factor receptor 3 (HER3) mRNA expression, and ≤2 prior chemotherapy lines. Investigators selected single-agent topotecan, gemcitabine or weekly paclitaxel before patients were randomized to either placebo or pertuzumab (840→420 mg every 3 weeks), stratified by selected chemotherapy, prior anti-angiogenic therapy, and platinum-free interval. Final overall survival analysis (key secondary end point) was pre-specified after 129 deaths. Patient-reported outcomes (secondary end point) were assessed at baseline and every 9 weeks until disease progression. Results: At database lock (June 9, 2016), 130 (83%) of 156 randomized patients had died. Median follow-up was 27 months in the pertuzumab arm versus 26 months in the control arm. In the intent-to-treat population there was no overall survival difference between treatment arms (stratified HR 0.90, 95% CI 0.61 to 1.32; p=0.60). Results in subgroups defined by stratification factors indicated heterogeneity similar to previous progression-free survival results. Updated safety was similar to previously published results. Compliance with patient-reported outcomes questionnaire completion was >75% for all validated patient-reported outcomes measures. Pertuzumab demonstrated neither beneficial nor detrimental effects on patient-reported outcomes compared with placebo, except for increased diarrhea symptoms. Discussion: Consistent with the primary results, adding pertuzumab to chemotherapy for low tumor HER3 mRNA-expressing platinum-resistant ovarian cancer did not improve overall survival, but showed trends in some cohorts. Except for increased diarrhea symptoms, pertuzumab had no impact on patient-reported outcomes. ClinicalTrials.gov: ClinicalTrials.gov: NCT01684878 .